Factors Influencing the Determination of Transfer Pricing That Moderates Inflation: Evidence from Multinational Manufacturing Companies Listed on the Indonesia Stock Exchange (2017–2024) - Asna Damayanti; Wiwik Pratiwi; Irzan Syahrial (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: This paper examines how corporate income tax, leverage, exchange rates, company size, profitability, and bonus mechanisms affect transfer pricing decisions. Inflation is included as a moderating variable. This study analyzes the interaction of these factors in the transfer pricing behavior of Indonesian multinational companies. Objective: The aim of this study was to examine the relationships among various financial and macroeconomic determinants affecting transfer pricing, with inflation acting as a moderating factor. Methods: Panel data regression and Moderated Regression Analysis (MRA)-based quantitative frameworks were used. The sample includes 19 multinational companies listed on the Indonesia Stock Exchange between 2017 and 2024, with a total of 152 observations. After specification testing, the random-effects model was selected as the best estimator for this study. Results: This study reveals that corporate income tax schemes and bonus mechanisms have a significant negative effect on transfer pricing. On the other hand, leverage, exchange rates, company size, and profitability do not partially affect transfer pricing. Transfer pricing behavior is largely explained by the independent variables. This research is characterized by the use of inflation as a moderating variable. Furthermore, the moderation analysis shows that inflation is a quasi-moderating factor that weakens the effect of corporate income tax. In contrast, inflation does not weaken the effects of leverage, exchange rates, company size, profitability, or the effectiveness of bonus mechanisms. Conclusion: These findings underscore the importance of fiscal pressures and managerial incentives in determining transfer pricing behavior, even across different macroeconomic environments.